The Influence of Digital Marketing and Brand Image on Purchasing Decisions at The Indomobil Plaza Dealer in Indramayu - Griesthalia Cantik Lusyana; Ika Nurjannah Nurjannah; Ihya Raihan Izzuddin; May Dedu (Politeknik Siber Cerdika Internasional, 2024)
This research aims to determine the extent to which digital marketing and brand image influence purchasing decisions. Employing a quantitative research method, data was gathered using research instruments and analyzed quantitatively and descriptively. A sample of 48 respondents was selected using the Slovin formula. Data analysis was conducted using the SPSS 25 software, which included validity tests, reliability tests, linearity tests, multicollinearity tests, and multiple linear regression analysis (including t-tests and f-tests). The findings indicate that both Digital Marketing (X1) and Brand Image (X2) have a positive and significant impact on Purchasing Decisions (Y) at the Nissan Indramayu car dealership. The hypothesis testing results for the two independent variables on the dependent variable reveal that digital marketing and brand image collectively influence purchasing decisions by 49.4%. The remaining 50.6% is affected by other factors not included in this regression model or by random variables.